Web Service Untuk Integrasi Sistem Informasi Penelitian UIN Sunan Kalijaga Yogyakarta - Daru Prasetyawan (Universitas Multi Data Palembang, 2026)
Data integration is a process to ensure the availability, accuracy, speed and accuracy of data by combining data from several different sources. Data integration is needed to align data, so that every different system will have the same data. Web service is a web application that is used to exchange messages/information via the internet. Interaction between applications or systems using a set of open standard protocols. This research method refers to the software development life cycle (SDLC) for developing web services. The web service was developed using the REST architecture for research data integration using PHP as the programming language and PostgreSQL as the DBMS. Testing is carried out to ensure that the web service can run as planned. Furthermore, the web service is applied to research information systems. The web service is used to facilitate communication between research information systems and other applications.